A Study on Speaking Anxiety of English Education Study Program Students at the University of Palangka Raya - Yoskapela; Susanty; Bahing; Ristati (The Study Program of English Education of Palangka Raya University, 2022)
English-speaking anxiety is a specific phenomenon in the context of English language learning which has debilitating consequences on EFL learners’ speaking skills if the condition is severe. Focusing on this issue, this study was intended to describe the levels of speaking anxiety of English Education Study Program’s fourth-semester students who are taking Advanced English-Speaking Course at University of Palangka Raya. To obtain the objective, the data were collected through observation, questionnaire, and documentation. The result of data analysis revealed that the participants mostly experience a moderate speaking anxiety level because their average number of speaking anxiety signs as observed is 2, and their average FLSAS score from the questionnaire is 53.83. As evidenced by the data distribution, 15 participants (42.9%) have a moderate level, followed by 14 participants (40.0%) who have a low level and 6 participants (17.1%) who have a high level. Furthermore, it can be inferred that the higher the level of speaking anxiety is, the lower the speaking score they have. Concerning this result, it is suggested that the lecturers should formulate teaching strategies to help students reduce their speaking anxiety. Likewise, students should be active in finding ways to alleviate their speaking anxiety level.